(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to determine the influence of school principal’s instructional leadership, teacher pedagogical competence, and teacher work motivation on the quality of learning, both partially and simultaneously. The research was conducted in SD Negeri in Tembalang District, Semarang City, with a sample of 186 teachers. This study utilized a quantitative correlational approach. Data were collected using the survey method, with questionnaires serving as the primary data collection tool. Responses were measured using a Likert scale. For statistical data processing and hypothesis testing, the researchers employed regression analysis, utilizing SPSS software. The findings indicate that instructional leadership, teacher pedagogical competence, and teacher work motivation individually exert a significant influence on the quality of learning, contributing 45.8%, 57%, and 60.8% to the variance, respectively. Most importantly, all three factors collectively and simultaneously influence the quality of learning, explaining 66.7% of its variance. The novelty of this research lies in its integrated framework, which simultaneously tests the combined effect of instructional leadership, teacher pedagogical competence, and work motivation on learning quality. By confirming the significant synergistic impact of these three critical factors, this study advances existing knowledge by providing a holistic empirical model.